The Use Of Word Card Media To Improve Sentence For Class V Students Of Elementary School Sihombu - Henri RH Hasugian (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
This research was conducted to improve the understanding of the fifth-grade students in composing sentences using word card media. The work process was carried out by forming cards as needed by containing the words on each piece of card. The procedure in the game was developed by dividing groups of students and the teacher supervising and giving directions. The research subjects were students of class V SD Sihombu. This research goes through several activities, namely planning, implementing, observing, and reflecting. The instruments used were observation sheets and test instruments. Based on the tests and analyses carried out, there was an increase in the quality of sentence arrangement for grade V students, namely in the first stage students / I compiled sentences without any assistance and produced an average value of 70. The second stage in the second trial the value reached 1652 with a rerate of 82.6 in the Very Good category and experiencing a very significant development.